ANALISA SISTEM PENTANAHAN TRANSFORMATOR - Irine Kartika Febrianti (Universitas PGRI Palembang, 2018)
Grounding is connecting a circuit or equipment to the earth. Poor earthing systems can lead to decreased quality of electric power. Studies of land is often underestimated, but a good grounding is very important.While doing research in substations gutter oil, load imbalance on a substation Gutter oil, causing the flow of each phase at # 3 60MVA power transformer 150/20 KVPT. PLN (Persero) substation Talang Kelapa Banyuasin become unbalanced that IR = 954.37 A, IS = 968.32, IT = 950.24 A. The amount of load imbalance (%) between each phase at # 3 60MVA power transformer 150/20 KV is 0.7412%,This is because the use of an uneven load. As a result of load imbalance between each phase at # 3 60MVA power transformer 150/20 kV, the current will flow in the neutral transformer IN = 16,40574Ð-72,59°.power loss due to the neutral current is 0.7073 W. neutral point voltage to ground -22.32 V. neutral current flowing to ground is 23.1768 A. power loss due to neutral current flowing to ground is 1 , 4116 W. current flowing to the ground from the second transformer is 22.23699 Ampere. Prisoners to the substation earthing gutter oil is R10,0692 Ω and R2 0,1856 Ω, while the resistance value of the grounding in a way parallel 1Ω, so either one very effective way to lose custody of land is to deepen the grounding electrodePentanahan adalah melakukan koneksi sirkuit atau peralatan ke bumi. Sistem pentanahan yang kurang baik dapat menyebabkan penurunan kualitas tenaga listrik. Ilmu pertanahan sering kali dianggap remeh, padahal pentanahan yang baik sangatlah penting. ketidakseimbangan beban menyebabkan arus tiap fasa pada Transformator daya #3 60MVA 150/20 KV menjadi tidak seimbang yaitu IR = 954,37 A, IS = 968,32, IT = 950,24 A. Besarnya ketidak seimbangan beban (%) antara tiap-tiap fasa pada Transformator daya #3 60MVA 150/20 KV adalah 0,7412 %, hal ini disebabkan karena penggunaan beban yang tidak merata. Sebagai akibat dari ketidakseimbangan beban antara tiap-tiap fasa pada Transformator daya #3 60MVA 150/20 KV maka akan mengalir arus di netral transformator IN = 16,40574Ð-72,59°. rugi-rugi daya akibat adanya arus netral adalah 0,7073 W. tegangan titik netral terhadap tanah -22,32 V. arus netral yang mengalir ke tanah adalah 23,1768 A. rugi-rugi daya akibat arus netral yang mengalir ke tanah adalah 1,4116 W.Arus yang mengalir ketanah dari kedua transformator adalah 22,23699 Ampere.Tahanan pentanahan adalah R10,0692 Ω dan R2 0,1856 Ω, sedangkan nilai tahanan pentanahan dengan cara parallel sebesar 1Ω, jadi salah Satu cara yang sangat efektif untuk menurunkan tahanan tanah adalah dengan memperdalam elektroda pentanahan.